Variability and controls of stable carbon isotopic fractionation during aerobic methane oxidation in temperate lakes - Thottathil, Shoji D.; Reis, Paula C. J.; Prairie, Yves T. (Frontiers in Environmental Science, 2022)
The aerobic oxidation of methane (CH4¬) by methanotrophic bacteria (MOB) is the major sink of this highly potent greenhouse gas in freshwater environments. Yet, the aerobic CH4 oxidation is one of the largest uncertain components in predicting the current and future CH4 emissions from these systems. While stable carbon isotopic mass balance is a powerful approach to estimate the extent of CH4 oxidation in situ, its applicability is constrained by the need of a reliable isotopic fractionation factor (αox), which depicts the discrimination of MOB against the heavier isotope during CH4 oxidation. Here we explored the natural variability and the controls of αox across the water column of six temperate lakes using experimental incubation of unamended water samples at different temperatures. We found a large variability of αox (1.004 to 1.038) with a systematic increase from the surface to the deep layers of lake water columns. Moreover, αox was strongly positively coupled to the abundance of MOB in the Gammaproteobacteria class (Gamma-MOB), which in turn correlated to the concentrations of oxygen and CH4, and to the rates of CH4 oxidation. To enable the applicability in future isotopic mass balance studies, we further developed a general model to predict αox using routinely measured limnological variables. By applying this model to δ13C-CH4 data obtained from the study lakes, we show that using a constant αox value in isotopic mass balances can largely misrepresent and undermine patterns of the extent of CH4 oxidation in lakes. Our αox model thus contributes towards more reliable estimations of stable carbon isotope-based quantification of CH4 oxidation and may help to elucidate large scale patterns and drivers of the oxidation-driven mitigation of CH4 emission from lakes.